2023
DOI: 10.3390/ijms24097683
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-3 as a Marker for Increased Thrombogenicity in COVID-19

Abstract: Galectin-3 is a beta-galactoside-binding lectin involved in inflammation and lung fibrosis and postulated to enhance thrombosis. In COVID-19, it is considered to be a prognostic marker of severity. The aim of this study was to evaluate whether galectin-3 is associated with thrombogenicity in COVID-19. Patients with moderate-to-severe COVID-19 (COVpos; n = 55) and patients with acute respiratory diseases, but without COVID-19 (COVneg; n = 35), were included in the study. We measured the amount of galectin-3, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…In addition, results from a study by Ozcan et al indicated that galectin-3, IL-6 and CRP levels on hospital admission are related to the need for transfer to the ICU and that galectin-3 alone is related to the need for advanced ventilatory support [14]. Galectin-3 was also studied in the context of thrombogenicity and was found to significantly correlate with von Willebrand Factor (vWF) and mean platelet volume (MPV) in a COVID-positive group as compared to a COVID-negative group, thus indicating platelet activation [17]. Our results confirm previous studies on galectin-3, using not only larger patient numbers, but two cohorts from different catchment areas.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, results from a study by Ozcan et al indicated that galectin-3, IL-6 and CRP levels on hospital admission are related to the need for transfer to the ICU and that galectin-3 alone is related to the need for advanced ventilatory support [14]. Galectin-3 was also studied in the context of thrombogenicity and was found to significantly correlate with von Willebrand Factor (vWF) and mean platelet volume (MPV) in a COVID-positive group as compared to a COVID-negative group, thus indicating platelet activation [17]. Our results confirm previous studies on galectin-3, using not only larger patient numbers, but two cohorts from different catchment areas.…”
Section: Discussionmentioning
confidence: 99%
“…Identifying reliable prognostic markers and therapeutic targets is crucial for improving patient outcomes [68]. One potential candidate is Gal-3, a protein involved in inflammation, lung fibrosis, and thrombogenicity [69,70]. Galectin-3 is a multifunctional protein that plays a crucial role in various biological processes, including inflammation, cell adhesion, and immune modulation [10].…”
Section: Sars-cov-2 Virus Infection and Galectin-3mentioning
confidence: 99%
“…Gal-3 levels correlate with inflammatory markers such as CRP, IL-6, and TNF-α, and monitoring these levels can help clinicians identify high-risk patients and guide clinical decision-making [73]. Galectin-3 also correlates with markers of thrombogenicity and clinical disease severity, suggesting its usefulness in assessing disease severity and hypercoagulability in COVID-19 patients [69]. In Table 2, we provide an overview of the diverse applications and implications of Gal-3 as a biomarker across different viral infections.…”
Section: Galectin-3 As a Potential Biomarker For Covid-19 Severity An...mentioning
confidence: 99%
See 1 more Smart Citation
“…Growth differentiation factor 15 (GDF-15) is an inflammatory biomarker belonging to the transforming growth factor ß superfamily. It is widely distributed in various organs, where it is secreted by macrophages, endothelial cells, and cardiomyocytes during oxidative stress, tissue injury, or inflammation [126,127]. Although the full effects of GDF-15 are not yet fully understood, it has shown potential cardioprotective effects.…”
Section: Gdf-15mentioning
confidence: 99%